Optimal dispatching control of EV aggregators for load frequency control with high efficiency of EV utilization. (1st August 2022) - Cai, Sinan; Matsuhashi, Ryuji
Abstract: Maintaining frequency stability in a power system with a large scale of renewable energy resources (RES) requires extra frequency regulation resources due to the intermittent generation of RES. As one of the most promising solutions, electric vehicles (EVs) have faster response characteristics and can provide considerable regulation capacity when aggregated. When participating in load frequency control (LFC), the EV aggregator needs to dispatch the LFC signal into every single EV. However, since the aggregated EVs have different travel profiles and state-of-charge (SOC), it is challenging for the aggregator to decide the dispatching method so that both regulation requirements and users' transport usage can be best satisfied. In this paper, an optimal dispatching control is designed for the EV aggregator. With the proposed control scheme, the EV aggregator can provide the regulation capacity to the system while ensuring that each individual EV will have enough SOC before the next trip. Compared with the optimal dispatching methods in existing literature, the proposed control operates at a faster time-step and allows EV aggregators to utilize EVs more efficiently, therefore more capacity payment from the market can be obtained by the EV aggregators. Simulation is performed in Matlab and Simulink to examine the performance and the effectiveness of the proposed dispatching controller. Graphical abstract: Highlights: Optimal dispatching scheduling to maximize the revenue from the LFC market. A faster dispatching time-step to utilize the EVs more efficiently for LFC. A specific GA is designed to solve the optimization problem relatively rapidly.